Outside: Let’s Promote Biodiversity - Soares, M. F.; Liz, R.; Ganço, I. (Open Schools Journal for Open Science, 2020)
The school Santa Marta do Pinhal opened in the academic year 2017/2018 with many expectations, but the reality caused some disappointment. The playground was small for so many children, and everything seemed impersonal, lifeless. It was necessary to act and the whole school community got involved. Class assemblies were held within all school groups, where problems were discussed and suggestions were made. This was followed by meetings of delegates, teachers, parents and local authorities, which led to new partnerships. Thanks to the enormous willingness, determination, commitment and resilience of all stakeholders, our school are now very different. The pond enchants kids and grownups, the flowerbeds, the aromatic spiral and the vegetable garden give life to the playground. Many of the classes are now OUTSIDE, willing to learn and where discoveries are made every moment.